2020
DOI: 10.21037/atm-20-5080
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab exerts anti-inflammatory activity in six critically ill COVID-19 patients: a retrospective analysis

Abstract: Background: Coronavirus disease 2019 has become a worldwide pandemic, affecting countries across the globe. With no current vaccine, treatment is still a critical intervention for minimizing morbidity and preventing disease-specific mortality. This study aimed to assess the clinical outcomes of critically ill COVID-19 patients using Tocilizumab treatment to provide recommendations for the treatment of COVID-19 patients with severe disease. Methods: This was a retrospective analysis of medical records of six c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A number of preclinical and clinical studies have confirmed the safety and efficacy of the IL6 antibody, siltuximab, and the IL6R antibodies, tocilizumab and sarilumab, showed promise in decreasing cytokine levels, ameliorating symptoms of systemic toxicity, and reducing the requirements for adjuvant and other therapies, including vasoactive drugs, glucocorticoids and respiratory support. 139 , 140 , 141 , 142 There are presently more than 30 trials investigating tocilizumab for treatment of SARS‐CoV‐2. Tocilizumab has been used for treatment of cytokine storms.…”
Section: Repurposing Clinically Available Drugs and Therapies For Pat...mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of preclinical and clinical studies have confirmed the safety and efficacy of the IL6 antibody, siltuximab, and the IL6R antibodies, tocilizumab and sarilumab, showed promise in decreasing cytokine levels, ameliorating symptoms of systemic toxicity, and reducing the requirements for adjuvant and other therapies, including vasoactive drugs, glucocorticoids and respiratory support. 139 , 140 , 141 , 142 There are presently more than 30 trials investigating tocilizumab for treatment of SARS‐CoV‐2. Tocilizumab has been used for treatment of cytokine storms.…”
Section: Repurposing Clinically Available Drugs and Therapies For Pat...mentioning
confidence: 99%
“…Through blocking cytokine production, ameliorating the symptoms of systemic toxicity, and reducing the requirements for adjuvant and other therapies, this antibody has shown high efficacy and safety in a series of preclinical and clinical studies involving SARS‐CoV‐2. 140 , 142 , 144 , 388 Up to now, there have been more than 30 SARS‐CoV‐2 trials (NCT04445272, NCT04730323, NCT04331795, so on) investigating tocilizumab as a COVID‐19 therapeutic. On June 24, 2021, tocilizumab was approved by the US FDA for the treatment of hospitalized adults and pediatric patients (over two years old) with severe symptoms of COVID‐19 (FDA News Release).…”
Section: Repurposed Drugs In Clinical Trialsmentioning
confidence: 99%
“…Even in children and adolescents, the so called ‘low-risk’ categories for COVID-19, inflammation- associated aggressive form of COVID-19 has been reported [ 45 ]. Clinical resolution of inflammation can possibly impact the survival of COVID-19 patients [ 46 ]. Several studies have indicated that SARS-CoV-2 causes injury predominantly through host immune dysregulation, increase in inflammation and/or hyperinflammation leading to severity of the disease, resulting in high rate of hospitalizations and mortality.…”
Section: Pulmonary Manifestations Of Covid-19mentioning
confidence: 99%
“…A number of studies have confirmed the safety and efficacy of the anti-IL-6 antibody siltuximab, and the anti-IL-6R antibodies tocilizumab and sarilumab (25)(26)(27). To date, more than 40 clinical trials using anti-IL-6 or anti-IL-6R treatments have commenced for patients with COVID-19, including more than 30 trials using tocilizumab (Table I).…”
Section: Targeted Cytokine Storm Therapy -The Fight Against Covid-19mentioning
confidence: 99%